Prostitution in the Context of Human Trafficking - PRAMONO, Bayu Aji; RAMADHANI, Sri Ridma; AIKO, Ovelia; SALAHIDIN; HELMI; DEBIANTHO (Indonesia Strategic Sustainability, 2023)
Purpose:The phenomenon of prostitution is currently ubiquitous among young people. Based on this reality, the phenomenon of prostitution needs to be studied theoretically from a sociological and legal perspective, which also affects the emergence of laws and regulations that regulate the issue of human trafficking and prostitution. The purpose of this study is (1) to examine theoretically from sociological and legal perspectives on human trafficking and (2) to determine the influence of laws and regulations on trafficking and prostitution.Methodology:This study is empirical by using primary data and secondary. Primary data is collected by observation and interviews directly with related sides. Sample specified in purposive sampling. Secondary data was obtained by passing the bibliography study and document with the descriptive analysis.Findings:This study is empirical by using primary data and secondary. Primary data is collected by observation and interviews directly with related sides. Sample specified in purposive sampling. Secondary data was obtained by passing the bibliography study and document with the descriptive analysis.Implication:The Law is no longer effective in controlling the social conditions of society. It can be seen from the many laws and regulations that regulate the problem of prostitution and trafficking but are unable to overcome the problems that occur. Economic conditions are the cause of this. Apart from that, something interesting about prostitution is that social control laws are no longer able to regulate it because, from an early age, women have been educated to work in places of prostitution or night entertainment.